Still Frugivorous: Temporal Feeding Behavior and Food Composition of Müller's Gibbon (Hylobates muelleri) in a Zoo Environment - Jeremia Frandy Apitalau; Florenchia Ersha Kurnia Putri; Laurentia Henrieta Permita Sari Purba (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
Understanding feeding behavior in captive primates is important for improving ex-situ conservation and animal welfare management. This study analyzed the feeding duration and food composition of captive Müller's gibbons (Hylobates muelleri) at Gembira Loka Zoo, Yogyakarta, Indonesia. Observations were conducted for 60 days using scan sampling at 1-minute intervals on one adult male and one adult female. Feeding duration for each food category was quantified and analyzed descriptively, while differences between individuals were evaluated using the Mann–Whitney test. Fruits constituted the largest proportion of the diet for both individuals. Adult males spent 60% of feeding duration consuming fruits, 15% tubers, and 17% leaves, whereas adult females spent 79% consuming fruits, 14% tubers, and 7% leaves. Statistical analysis indicated no significant difference in feeding duration between individuals. The findings demonstrate that captive feeding practices generally reflect the frugivorous tendencies of Müller’s gibbons observed in natural habitats. This study contributes preliminary information for improving dietary management, ex-situ conservation strategies, and contextual biology learning related to animal behavior and conservation.